Bulbophyllum putaoensis (Orchidaceae: Epidendroideae; Malaxideae), a new species from Kachin State, Myanmar - Liu, Qiang; Zhou, Shi-Shun; Li, Ren; Zhang, Ming-Xia; Zyaw, Myint; Lone, Shwe; Quan, Rui-Chang (Phytotaxa, 2017)
The orchid flora of Myanmar is highly diverse but as yet poorly known in the continental Asia, which is largely a result of periods of past instability and political isolation of the country. Also the remoteness of many orchid-rich areas and the difficulties of investigation in rugged terrain have also played a role (Ormerod & Kumar, 2003; Kurzweil & Lwin, 2014). According to recent estimates about 800 orchid species are distributed in Myanmar (Kurzweil & Lwin, 2014), which were probably underestimated. Many new distribution records and new species have been published in the last few years (Ormerod, 2002, 2006, 2012; Ormerod & Kumar, 2003, 2008; Ormerod & Wood, 2010; Nyunt, 2006; Kurzweil et al., 2010; Kurzweil & Lwin, 2012a,b; Tanaka et al. 2011).